Impact of attachment behavior on the treatment process of chronic pain patients - Pfeifer, Ann-Christin; Ehrenthal, Johannes C.; Neubauer, Eva; Schröter, Corinna; Schiltenwolf, Marcus (Journal of pain research, 2018)
Background: Insecure attachment patterns are related to the onset and development of chronic pain. However, it is less documented on how short- and long-term effects of pain therapy might differ with the attachment style in interaction with specific pain conditions. We therefore examined how two different groups of chronic pain patients differ in their treatment trajectories and in regard to attachment.Method: N=85/76/67 (T1/T2/T3) patients with medically unexplained musculoskeletal pain (UMP group) were compared to n=89/76/56 patients with joint pain from osteoarthritis (OA group), using multilevel modeling. UMP patients received a multimodal pain program, and OA patients received surgery. Pain intensity before (T1) and after (T2) treatment and at a 6 months follow-up (T3) was assessed by using a visual analog scale of pain.Results: Pain patients report a significant reduction in pain intensity upon the completion of the treatment compared to T1. Over the next 6 months, the pain intensity has further declined for patients with low attachment anxiety. In contrast, patients with highly anxious attachment report an increase in pain intensity. This main effect of anxious attachment on pain is significant when predicting changes both in acute treatment and during follow-up while controlling for group effect. In addition, there is also an interactive effect of group by avoidant attachment. In the UMP group, high scores in avoidant attachment were associated with the lower reduction in pain severity, while in the OA group, high scores in attachment avoidance were associated with a steeper reduction in pain severity.Conclusion: The results indicate that insecurely attached patients with pain symptoms only benefit from a multimodal pain therapy in limited ways in regard to posttreatment trajectories. Maintaining positive results over a period of 6 months is a challenge, compared with securely attached patients.Significance: The results of this study suggest the importance of direct and indirect mechanisms of attachment and its relevance for the management of pain experiences. Therefore, to include the individual attachment patterns in the treatment may be a promising way to enhance the treatment prospects.Keywords: attachment theory, chronic pain, multimodal treatment